Virtual breakout rooms: an effective approach to offer guidance to medical students on residency applications (Canadian Medical Education Journal, 2021)
Implication statementPeer mentorship on residency applications has been difficult due to recent public health measures, prompting a shift from in-person events to virtual platforms. To address gaps in career exploration, we created a virtual, non-recorded space that allowed medical students and residents to discuss the Canadian Resident Matching Service (CaRMS) process meaningfully and transparently. Attendees reported a greater understanding of the match process and reduced anxiety after the event. This model provides a virtual framework that can be adapted for various mentorship opportunities.